Simulation of DG Systems Composed with Solar Photovoltaic and a Micro-Turbine in Remote Areas: Improved stability and performance of DG systems in remote areas (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rapid depletion of fossil fuel resources on a worldwide basis has necessitated an urgent search for alternative energy sources to cater to the present days’ demand. Nevertheless, the action of PV array is unsteady as there is instability of radiation and temperature, and hence it is compulsory to combined work with governable power generation unit to enhance the stability of the entire system. A micro grid distributed generation system based on direct current bus has been considered comprising of PV power generation unit, micro turbine power generation unit, DC-DC converter and inverter unit. The photovoltaic energy is vastly dependent on environmental condition such as ambient temperature and insolation. The limitation of above said system is overcome by integrating MTG system. Thus load voltage variation is found to be in the acceptable range. This Micro grid system can withstand the disturbance in the load as well as the climatic conditions, and nullifies the problems of these variations at the supply voltage. This micro grid topology gives good performance under change in insolation, ambient temperature and load variation. This proposed micro grid topology can be used for isolated power generation in standalone areas or remote isolated groups.